Implementation of Academic Supervision by the Head of Madrasah in Improving Teacher Performance (A Case Study at Raudhatul Athfal (RA) Al-Hikmah Mustopa, Plered Village, Plered District) - Nani Mulyani; Amit Saepul Malik; Dede Supriyatna (Manajia: Journal of Education and Management, 2026)
This study aims to analyze the implementation of academic supervision by the madrasah principal in improving teacher performance at Raudhatul Athfal (RA) Al-Hikmah Mustopa, as well as to identify the supporting factors, inhibiting factors, and its impact on the quality of learning. This research employed a qualitative approach using a case study method. The research subjects consisted of the madrasah principal and teachers. Data were collected through interviews, observation, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that academic supervision was implemented through supervision program planning, participatory and collaborative supervision practices, and follow-up activities in the form of coaching and teacher performance evaluation. Supporting factors included the principal’s commitment, peer support, and adequate facilities and infrastructure. Meanwhile, inhibiting factors involved time constraints, teachers’ administrative workload, and limited advanced training. The impact of academic supervision was reflected in improvements in lesson planning, teaching skills, and teachers’ motivation.